2012
DOI: 10.1002/app.38466
|View full text |Cite
|
Sign up to set email alerts
|

Electrocatalysis and detection of nitrite on a polyaniline‐Cu nanocomposite‐modified glassy carbon electrode

Abstract: A polyaniline (PANI)-Cu nanocomposite-modified electrode was fabricated by the electrochemical polymerization of aniline and the electrodeposition of copper under constant potentials on a glassy carbon electrode (GCE), respectively. Scanning electron microscope result shows that the PANI-Cu composite on the surface of the GCE displays the nanofibers having an average diameter of about 80 nm with lengths varying from 1.1 to 1.2 lm. The electrode exhibits enhanced electrocatalytic behavior to the reduction of ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 28 publications
(22 reference statements)
0
10
0
1
Order By: Relevance
“…When the modified electrode was immersed in a solution of potassium hexacyanoferrate (III), K 3 [Fe(CN) 6 ], a pair of redox peaks appeared at potential of 0.68 − 0.72 V attributed to the Fe II /Fe III pair in the complex Cu 2 [Fe(CN) 6 ] formed within the polymeric film. Several works reported the application of copper polymeric films in determination of sulfite and nitrite but problems with repeatability and control of the amount of copper deposited on the electrode surface limits its use . In this work, Cu(II)MA‐based copolymers are presented as excellent option to manufacture of GCE modified with copper polymer that allows to increase the amount of copper on the electrode surface, which could improve the sensibility, lifetime, repeatability, and precision of the electroanalytical method.…”
Section: Resultsmentioning
confidence: 99%
“…When the modified electrode was immersed in a solution of potassium hexacyanoferrate (III), K 3 [Fe(CN) 6 ], a pair of redox peaks appeared at potential of 0.68 − 0.72 V attributed to the Fe II /Fe III pair in the complex Cu 2 [Fe(CN) 6 ] formed within the polymeric film. Several works reported the application of copper polymeric films in determination of sulfite and nitrite but problems with repeatability and control of the amount of copper deposited on the electrode surface limits its use . In this work, Cu(II)MA‐based copolymers are presented as excellent option to manufacture of GCE modified with copper polymer that allows to increase the amount of copper on the electrode surface, which could improve the sensibility, lifetime, repeatability, and precision of the electroanalytical method.…”
Section: Resultsmentioning
confidence: 99%
“…Various electrode modifications, mainly in the form of thin layers on a glassy carbon substrate electrode (e.g. poly(3,4-ethylenedioxythiophene)/graphene nanocomposite, polyaniline/Cu nanocomposite and reduced graphene/ Pd nanocomposite to name a few), have been proposed [28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…Conducting polymer-metal nanocomposites, a new class of materials, offers device design possibility with new functionality, in which the optimized properties of both organic and inorganic have been exploited [169][170][171][172][173][174][175]. Many appealing studies have been reported in literatures based on nanocomposites of PANI with different metals such as PANI-Ag [176,177], PANI-Au [178][179][180], PANI-Pt [181][182][183] and PANI-Cu [184,185]. PANI-Ag is one of the extensively considered nanocomposites because ease of preparation by in-situ approach i.e.…”
Section: Polyaniline-silver Nanocompositementioning
confidence: 99%